The Reliability of Evaluating Masticatory Function by Masticatory Analysis - Shiga, Hiroshi; Miyazaki, Jin; Kobayashi, Yoshinori (Nihon Hotetsu Shika Gakkai Zasshi, 2001)
Purpose: To clarify the reliability of evaluating masticatory function, the stability of the masticatory movement of healthy subjects and TMD (Temporomandibular disorders) patients were analyzed. Methods: The indicators used were SD/OD (standard deviation/opening distance) of lateral components of opening and closing, and of the vertical component, which show stability of path; the coefficient variation of opening, closing, occluding, and cycle time, which shows stability of rhythm, and SD/OD of the velocity component of opening and closing, which shows stability of velocity. A normal range was established from data of 50 healthy subjects (group A). Then another 50 healthy subjects (group B) and 50 TMD patients (TMD group) were used, to analyze the degree of specificity and sensitivity. Results: The TMD group had much higher values than group A and group B (p<0.01). Because it was possible to make all subjects of group A fall into the normal range by taking at least 2 indicators for path, at least 3 indicators for rhythm, and at least 1 indicator for velocity, these numbers of indicators were used as the standard for determining the stability of masticatory movement. Evaluating the specificity and sensitivity of group B and the TMD group by path, rhythm, and velocity, each of them individually showed a value greater than 72%, except for sensitivity of velocity stability. Evaluating by any two indices, the value was greater than 80%, and when all three indices were used together, the value was greater than 90%. Conclusions: It was concluded that it is more reliable to evaluate masticatory function with all of the indicators for stability of movement path, movement rhythm, and movement velocity, than with just one or two of the indicators.